Growth, carcass and boar-odor traits in male pigs fed altrenogest - Jeffrey S Stevenson; E F Kluber III; J Ernest Minton; Duane L Davis; Melvin C Hunt; D S Pollmann; Jim L Nelssen (Kansas Agricultural Experiment Station Research Reports, 1986)
Two experiments were conducted to examine the effects of a synthetic progestogen (altrenogest) on growth and carcass characteristics of boars. Altrenogest inhibited both the growth of the testes and the pubertal rise in testosterone that is associated with maleness. Growth rate, feed intake, and feed/gain were unaffected by feeding altrenogest in both experiments; however, in Exp. 2. growth rate and feed intake during the 4-wk withdrawal of altrenogest were less than those in the control boar or barrow groups. These changes appeared to be related to marked mounting activity of boars beginning 5 days after withdrawal of altrenogest from the feed. Feeding altrenogest to growing boars had no negative effects on carcass qualitative traits, but intensity of boar odor in fat was not diminished in treated boars. It is possible that altrenogest would have to be fed until about 1 wk before slaughter or later to allow marketing of boars without significant boar odor.; Swine Day, Manhattan, KS, November 20, 1986
Keywords: Swine day; 1986; Kansas Agricultural Experiment Station contribution; no. 87-133-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 507; Swine; Growth; Carcass; Boar-odor; Altrenogest